Quantitative trait loci analysis for seed quality traits in sunflower (Helianthus annuus L.) recombinant inbred lines: QUANTITATIVE TRAIT LOCI ANALYSIS FOR SEED TRAITS IN SUNFLOWER RECOMBINANT INBRED LINES - J VANITHA; N MANIVANNAN; R CHANDIRAKALA; S ABIRAMI (Journal of Oilseeds Research, 2017)
The present investigation was carried out in sunflower F2:5 progenies of a cross TNHSF239-68-1-1-1 x 17B to identify the markers associated with seed quality traits. In this study, the QTL mapping work was based on the genotyping data obtained in the segregating population for the publicly available ORS markers previously mapped was used. In ICIM, the QTL analysis resulted into five QTLs viz., volume weight, seed colour, strips on margin, pollen colour and oil content. The QTL for volume weight had a LOD of 2.93 and 24.86 per cent of phenotypic variation with the flanking markers ORS471 and ORS1265 on chromosome 7. The QTL for seed colour was formed on chromosome 11 had a LOD of 36.58 and 96.46 per cent of phenotypic variation with the flanking markers ORS707 and ORS503. The QTL for strips on margin wasformed on chromosome 10 had a LOD of 3.23 and 63.88 per cent of phenotypic variation with the flanking markers ORS502 and ORS1037. The QTL for pollen colour had a LOD of 64.52 and 97.94 per cent of phenotypic variation with the flanking markers ORS707 and ORS503 on chromosome 11. The QTL for oil content was formed on chromosome 8 had a LOD of 2.51 and 28.99 per cent of phenotypic variation with the flanking markers ORS537 and ORS613. Hence the QTL identified for seed quality traits with closely linked markers may be exploited for the genetic improvement of sunflower genotypes through marker assisted selection.